Balneotherapy for Fibromyalgia Syndrome: A Systematic Review and Meta-Analysis - Cao, Chun-Feng (J Clin Med, 2021)
(1) Background: The efficiency of balneotherapy (BT) for fibromyalgia syndrome (FMS) remains elusive. (2) Methods: Cochrane Library, EMBASE, MEDLINE, PubMed, Clinicaltrials.gov, and PsycINFO were searched from inception to 31 May 2020. Randomized controlled trials (RCTs) with at least one indicator were included, i.e., pain, Fibromyalgia Impact Questionnaire (FIQ), Tender Points Count (TPC), and Beck’s Depression Index (BDI). The outcome was reported as a standardized mean difference (SMD), 95% confidence intervals (CIs), and I(2) for heterogeneity at three observational time points. GRADE was used to evaluate the strength of evidence. (3) Results: Amongst 884 citations, 11 RCTs were included (n = 672). Various BT regimens were reported (water types, duration, temperature, and ingredients). BT can benefit FMS with statistically significant improvement at different time points (pain of two weeks, three and six months: SMD = −0.92, −0.45, −0.70; 95% CI (−1.31 to −0.53, −0.73 to −0.16, −1.34 to −0.05); I(2) = 54%, 51%, 87%; GRADE: very low, moderate, low; FIQ: SMD = −1.04, −0.64, −0.94; 95% CI (−1.51 to −0.57, −0.95 to −0.33, −1.55 to −0.34); I(2) = 76%, 62%, 85%; GRADE: low, low, very low; TPC at two weeks and three months: SMD = −0.94, −0.47; 95% CI (−1.69 to −0.18, −0.71 to −0.22); I(2) = 81%, 0; GRADE: very low, moderate; BDI at six months: SMD = −0.45; 95% CI (−0.73 to −0.17); I(2) = 0; GRADE: moderate). There was no statistically significant effect for the TPC and BDI at the remaining time points (TPC at six months: SMD = −0.89; 95% CI (−1.85 to 0.07); I(2) = 91%; GRADE: very low; BDI at two weeks and three months: SMD = −0.35, −0.23; 95% CI (−0.73 to 0.04, −0.64 to 0.17); I(2) = 24%, 60%; GRADE: moderate, low). (4) Conclusions: Very low to moderate evidence indicates that BT can benefit FMS in pain and quality-of-life improvement, whereas tenderness and depression improvement varies at time phases. Established BT regimens with a large sample size and longer observation are needed.